APPLICATION OF BIOSTIMULATORS IN DYSFUNCTION OVARIES IN COWS - Bodnar, Oleksandr (Podilian Bulletin: Agriculture, Engineering, Economics, 2022)
Monitoring of obstetric and gynecological diseases of cows in dairy farms of the Podolsk region was carried out. The results of research show that ovarian dysfunction in cows in the structure of genital pathology is about 70%, and hypofunction and persistence of the ovarian corpus luteum account for an average of more than 45% of cases. infertile females. The paper provides a theoretical justification and a clinical trial of complex complex-sequential treatment regimens of cows with gonadal dysfunction: first, animals were injected three times with drugs of general stimulating action (colostrum, a mixture of colostrum with the drug ASD-f-2), then - hormonal drug "folligon". It was found that the addition to colostrum of 5% of the drug ASD-f-2, followed by freezing allows you to store it as a biostimulator for 6 months or more. According to the results of treatment, paravaginal administration of colostrum and its combination with ASD-f-2 is a highly effective and environmentally safe method of stimulating therapy, provides a higher gonadotropic effect of "folligon" and restores the reproductive function of cows with ovarian hypofunction and increases their ovarian function. The obtained data suggest that the proposed colostotherapy, having a general stimulating effect on the body, activates metabolic processes and significantly positively affects the mechanism of neurohumoral regulation of the sexual cycle in the direction of its normalization, helps to restore the function of the hypothalamic-pituitary system. fertility of cows